2022
DOI: 10.1101/2022.10.04.22280705
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Graphene Field Effect Biosensor for Concurrent and Specific Detection of SARS-CoV-2 and Influenza

Abstract: The SARS-CoV-2 pandemic has highlighted the need for devices capable of carrying out rapid differential detection of viruses that may manifest similar physiological symptoms yet demand tailored treatment plans. Seasonal influenza may be exacerbated by COVID-19 infections, increasing the burden on healthcare systems. In this work, we demonstrate a technology, based on liquid-gated graphene field-effect transistors, for rapid and ultraprecise detection and differentiation of influenza and SARS-CoV-2 surface prot… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…60 Addressing metal ion contamination, Kumar et al replaced FeCl 3 with (NH 4 ) 2 S 2 O 8 , enhancing GFET biosensors for detecting novel coronavirus and influenza with 88 zM and 227 zM. 61 To mitigate PMMA residue effects, thermal treatment and Ar plasma treatment have been explored. Yu et al 49 demonstrated solvent and impurity removal by annealing in high-purity Ar (Figure 2a), while Yang Cheng's group 50 improved sensitivity (LoD of 10 aM) by using Ar plasma to volatilize PMMA, presenting nondestructive graphene cleaning albeit with greater complexity (Figure 2b).…”
Section: Synthesis Of Graphene Channel In Gfet Biosensorsmentioning
confidence: 99%
See 3 more Smart Citations
“…60 Addressing metal ion contamination, Kumar et al replaced FeCl 3 with (NH 4 ) 2 S 2 O 8 , enhancing GFET biosensors for detecting novel coronavirus and influenza with 88 zM and 227 zM. 61 To mitigate PMMA residue effects, thermal treatment and Ar plasma treatment have been explored. Yu et al 49 demonstrated solvent and impurity removal by annealing in high-purity Ar (Figure 2a), while Yang Cheng's group 50 improved sensitivity (LoD of 10 aM) by using Ar plasma to volatilize PMMA, presenting nondestructive graphene cleaning albeit with greater complexity (Figure 2b).…”
Section: Synthesis Of Graphene Channel In Gfet Biosensorsmentioning
confidence: 99%
“…Reproduced with permission. 61 Copyright 2023, ACS Nano. (e) Bilayer graphene is functionalized through a low-damage nitrogen plasma treatment, and then further modified with specific antibodies to enable a label-free detection of CTCs.…”
Section: Synthesis Of Graphene Channel In Gfet Biosensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the detection limits of FET-based sensors have been pushed to ultralow concentrations (i.e., femto-molar or less) by adapting nanoscale materials such as nanowires [9,10], In 2 O 3 [7], and graphene [11][12][13]. The progress in this direction promises new applications for FET-based sensor technologies in drug discovery [14,15] and clinical diagnostics [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%